2019
DOI: 10.30880/ijie.2019.11.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Marble Particle on Physico-Mechanical Behaviour of Glass Fiber Reinforced Epoxy Composites

Abstract: Materials with superior properties have been used to meet the demand for better operational performance in the world of advanced science and technology. To fulfill such needs, the importance of industrial usage of polymer composite materials filled with industrial waste instead of high cost ceramic filler has tremendously increased. In this present work, new classes of glass fiber reinforced epoxy composites with different weight content of marble powder are prepared by simple hand layup technique. Different m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…According to Wang et al [42] chemically treated jute fibers composites attributed the enhanced properties like tensile strength, void-fraction, and interfacial adhesion compared to raw jute composites. Ray et al [43] found about 28 % improvement in impact strength of hybrid composite due to inclusion of 15% marble filler [44]. Latif et al stated that the inclusion of silica enriched rice husk ash enhanced the yield as well as ultimate strength of the fabricated composites.…”
Section: Introductionmentioning
confidence: 99%
“…According to Wang et al [42] chemically treated jute fibers composites attributed the enhanced properties like tensile strength, void-fraction, and interfacial adhesion compared to raw jute composites. Ray et al [43] found about 28 % improvement in impact strength of hybrid composite due to inclusion of 15% marble filler [44]. Latif et al stated that the inclusion of silica enriched rice husk ash enhanced the yield as well as ultimate strength of the fabricated composites.…”
Section: Introductionmentioning
confidence: 99%